The Making of Historian’s Virtues: A Critique of Hayden White’s Practical Historiography - Masood, Danyal (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article deals with the intellectual contribution of Hayden White around philosophy of historiography, historical theory, the virtues of epistemic representation, the question of what ought to be in historical discourse and cultural theory. This study analyzes to understand White own effected and effective consciousness in the historical context of twentieth century intellectual culture of postmodernism. White writings completely shifted the discourse of historical studies. His writings produce epistemic shift through cultural turn which not only transform historical understanding but other fields in humanities and social sciences. This study tried to understand White’s epistemic and ethical virtues of transcultural, narrative history, history as thought process, philosophy of historiography, de-idealizing histories through cultural and historiographical analysis. This study includes White’s experiences of truth, historiographical hopes, epistemic freedom, which are accessible through historiological efforts in the context of cultural materialism. This study has uses splinters theories and methods. These are hermeneutics, historiographic critique and cultural tools e.g. discourse analysis and historical reconstruction theory. It helps how his intellectual expedition shapes his historical ideas.